The social paradoxes of commercial surrogacy in developing countries: India before the new law of 2018 - Virginie Rozée; Sayeed Unisa; Elise de La Rochebrochard (BMC Women's Health, 2020)
Abstract Background Commercial surrogacy is a highly controversial issue that leads to heated debates in the feminist literature, especially when surrogacy takes place in developing countries and when it is performed by local women for wealthy international individuals. The objective of this article is to confront common assumptions with the narratives and experiences described by Indian surrogates themselves. Methods This qualitative study included 33 surrogates interviewed in India (Mumbai, Chennai and New Delhi) who were at different stages of the surrogacy process. They were recruited through five clinics and agencies. This 2-year field study was conducted before the 2018 surrogacy law. Results Surrogates met the criteria fixed by the national guidelines in terms of age and marital and family situation. The commitment to surrogacy had generally been decided with the husband. Its aim was above all to improve the socioeconomic condition of the family. Women described surrogacy as offering better conditions than their previous paid activity. They had clear views on the child and their work. However, they declared that they faced difficulties and social condemnation as surrogacy is associated with extra-marital relationships. They also described a medical process in which they had no autonomy although they did not express complaints. Overall, surrogates did not portray themselves as vulnerable women and victims, but rather as mothers and spouses taking control of their destiny. Conclusions The reality of surrogacy in India embraces antagonistic features that we analyze in this paper as “paradoxes”. First, while women have become surrogates in response to gender constraints as mothers and wives, yet in so doing they have gone against gender norms. Secondly, while surrogacy was socially perceived as dirty work undertaken in order to survive, surrogates used surrogacy as a means to upward mobility for themselves and their children. Finally, while surrogacy was organized to counteract accusations of exploitation, surrogates were under constant domination by the medical system and had no decision-making power in the surrogacy process. This echoes their daily life as women. Although the Indian legal framework has changed, surrogacy still challenges gender norms, particularly in other developing countries where the practice is emerging.